Neurologic Disease Is a Risk Factor for Revision After Lumbar Spine Fusion. Issue 6 (September 2019) - Glassman, Steven D.; Carreon, Leah Y.; Dimar, John R.; Gum, Jeffrey L.; Djurasovic, Mladen
Study Design: Medicare database analysis. Objective: The purpose of this study was to investigate whether neurologic disorders represent a risk factor for revision after lumbar spine surgery. Methods: Patients who underwent lumbar spine surgery were identified from 5% Medicare Part B claims between 2005 and 2008. Cox regression analysis was used to evaluate risk factors for revision within the 7 years after the index lumbar surgery. Covariates included age, gender, race, census region, Medicare buy-in status, Charlson score, year, prior lumbar fusion within 2 years of index surgery, prior diagnosis of cervical spondylotic myelopathy treated with or without cervical spine surgery, and diagnoses of other neuromuscular conditions. Results: Of 8665 cases who had decompression only, 401 (5%) had a revision within 7 years after the index surgery. Factors predictive of revision were prior lumbar fusion (hazard ratio [HR] = 2.78, confidence interval [CI] = 1.43-5.37, P = .002) and being female (HR = 1.61, CI = 1.31-1.97, P < .001). Of 5501 cases who had a decompression and fusion, 752 (14%) had a revision surgery within 7 years after the index surgery. Factors predictive of revision were the presence of a neurologic disorder (HR = 1.24, CI = 1.05-1.46, P = .010), prior lumbar fusion (HR = 3.09, CI = 2.05-4.63, P < .001), and being female (HR = 1.35, CI = 1.15-1.57, P < .001). Conclusions: An increase in revision rate ( P = 0.01, HR = 1.24) was seen in patients with neurologic disorders undergoing lumbar decompression and fusion, although not for patients undergoing decompression alone. This suggests an opportunity to improve clinical outcome and reduce revision rate through improved surgical decision making or treatment of the neurologic disorder.